The dynamics of Ireland's net external position - Lane, Philip R. (Statistical and Social Inquiry Society of Ireland, 2012)
Ireland's net external liability position expanded in dramatic fashion during 2008-2010, despite relatively small net financial flows during this period. Understanding the source and persistence of this negative shock is critically important in assessing the future path for the Irish economy. However, data analysis is made difficult by the confounding impact of Ireland?s major role as an international financial centre, such that the ?core? international balance sheet remains obscure. However, there is considerable indirect evidence to believe that a substantial component of this decline is genuine and relates to the internationally-leveraged structure of the financial portfolios of domestic Irish residents.
read before the Society, 24 November 2011
Keywords: net external position; Ireland; valuation; 314.15